ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Consumer Goods yang terdaftar di BEI pada Tahun 2012-2016) - Ardiana, Erna; Chabachib, Mochammad (Diponegoro Journal of Management, 2018)
The  company's  goal  is  to  maximize  shareholder  value  as  measured  by  the company's stock price that affects the value of the company. This study aims to analyze the factors that affect firm value (PBV) in consumer goods company that is listed on the Indonesia Stock Exchange period of 2012-2016. Independent variables used in study are capital structure (DER), firm size, liquidity (CR) and profitability (ROE) as an intervening variable.The population used in this study are all companies engaged in consumer goods company  which  is  listed  on  Indonesia  Stock  Exchange  (IDX)  period  of  2012-2016. Sampling  in this  study using  purposive sampling  which resulted  in a sample into  30 companies of consumer goods sectors. The analysis technique used is Path Analyst which is a development of the bivariate and multiple regression analysis.The results of this study showed that firm size and liquidity have a positive effect and significant to profitability, capital structure has a negative effect and insignificant to profitability. Profitability and firm size have a positive effect and significant to firm value. Capital structure and liquidity have a positive effect and insignificant to firm value. Profitability is able to mediate the effect of firm size and liquidity on firm value. But profitability is not able to mediate the effect of capital structure on firm value.